PENGARUH MODAL PSIKOLOGI DAN MOTIVASIKERJA TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (Studi BPTIKP Dinas Pendidikan Provinsi Jawa Tengah) - Sukiman, 1242020116 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study to analyze and determine the influence of psychology, work motivation, job satisfaction and organizational commitment on employee performance in office BPTIKP Central Java Provincial Education Department. Data used are primary and secondary data. All employees amounted to 92 people research sample. Methods of data collection using the questionnaire. Test the validity of the questionnaire using factor analysis and reliability test using Cronbach Alpha. Test the hypothesis using multiple linear regression. The study concluded: (1) capital psychology no significant effect on job satisfaction; (2) Work motivation and significant positive effect on job satisfaction; (3) psychological capital no significant effect on organizational commitment of employees; (3) work motivation and significant positive effect on organizational commitment; (4) job satisfaction does not significantly influence the organizational commitment of employees; (6) capital psychology positive and significant impact on the performance of employees; (7) work motivation no significant effect on the performance of employees; (8) job satisfaction does not significantly influence the performance of employees; (9) organizational commitment no significant effect on the performance of employees. Keywords : psychology capital, work motivation, job satisfaction, organizational commitment and employee performance